Research progress of auricular acupoint therapy for chronic gastritis - TIAN, Xiaodong; HUANG, Yanping; ZHOU, Sijia; LIU, Chang (Chinese Journal of Integrative Nursing, 2021)
As a traditional medical method in China, auricular therapy has simple operation and accurate curative effect. Chronic gastritis belongs to the categories of "epigastric pain", "hiccup", "acid vomiting" and "stupidity" in Traditional Chinese Medicine. It is mostly caused by mental stimulation and long-term improper diet. This paper expounded the overview of chronic gastritis, the overview of auricular therapy and the research of auricular therapy, and summarizes the new idea of auricular comprehensive therapy in the treatment of chronic gastritis, so as to serve the clinic. (耳穴疗法作为祖国传统医疗方法, 操作简单, 疗效确切。慢性胃炎属中医“胃脘痛”“呃逆”“吐酸”“纳呆”等范畴, 多由精神刺激, 长期饮食不节所致。本文从慢性胃炎疾病概述、耳穴治疗概述、耳穴疗法的研究等方面进行阐述, 总结耳穴综合疗法治疗慢性胃炎的相关经验, 以服务临床。)